(untitled) (INNOVATIVE ECONOMY, 2019)
Dovhan Zh.M. DEVELOPMENT OF BANKING ECOSYSTEMS: RISKS AND PROSPECTS Purpose. The aim of the article is determination of peculiarities of development of financial (banking) ecosystems, and first of all, assessment of threats and opportunities of their creation in domestic practice in the conditions of rapid development of financial technologies. Methodology of research. The theoretical basis of the research is the scientific works of foreign and domestic scientists on the problem under study. The following methods are used in the writing of the article: analysis and synthesis – in the study of foreign and domestic experience of creating ecosystems in banks; settlement and analytical – in the analysis of investments in financial technology; abstract and logical – in substantiation of theoretical generalizations and conclusions. Findings. The problems of banks’ activities in the form of ecosystems are investigated, because today the banks are faced with the choice to work according to the traditional scheme or to choose a new way of functioning as an ecosystem, the effectiveness of which depends on the correct choice of innovative business model and platform. The concepts of “portal”, “platform” and “ecosystem” have been delineated and the main components on which the bank’s ecosystem should be based are characterized, which will enable the bank to be competitive among other financial and non-financial organizations. The risks and opportunities of banking ecosystems functioning, as well as new key tasks and skills in the field of ecosystem organization, are identified. Originality. It is substantiated that the key competitive advantage of banks is the development of digital ecosystems and the proper positioning of themselves in them, with banks focusing on their three strengths: the use of know-how to present even complex financial products and processes; offers new services in the field of safe storage of money (personal and behavioural data); use of considerable experience in the field of regulation. Practical value. The results of the study can be taken into account by banking institutions, as the new ecosystem puts the end consumer at the first place, which necessitates a redevelopment of their internal processes and services to be more customer-centric in the digital ecosystem. Key words: bank; ecosystem; financial technologies; financial supermarket; FinTech (Financial technology) of the company; bank ecosystem; business model; portal; platform.